Effects of smail volumes of blood, isotonic and hypertonic saline administrations on haematological parometers and electrolytes in experimentally induced haemorrhagic shock in dogs - Ercan Keskin; Mursayettin Eksen (Eurasian Journal of Veterinary Sciences)
In this study, the effects of smail volumes of blood, isotonic and hypertonic saline administrations in dogs with haemorrhagic shock induced experimentally were investigated. For this purpose totally 20 dogs were usedas a material. The dogs were divided into 4 groups each of 5 dogs. the dogs were anesthetized with thiopenthal sodium (30 mg/kg, iv), and then haemorrhagic shock was performed experimentally. The mean artarial pressura (MAP) was reduced to 40+5mmHg and maintained at this /eve/ for 30 min (hypotensive period). At the end of the hypotensive period, the dogs of the group I,II,III and IV were treated by bo/us injection of 5ml/kg of blood, isotonic, 3.5% and 7.5% NaCl, respectively. The blood samples for the determination of hemogram were taken before the experiment, at the end of the hypotensive period and after treatment at 30 th, 60th and 90th mins. Before the experiment, the mean values of RBC, in group I,II,III and IV were found to be 5.37, 6.38, 5.58 and 6.23x106/mm3, respectively. This values were fo und to be 4.98, 6.00, 4,71 and 5.35x106/mm3, at the end of the hypotensive period, respectively. After the bo/us injection, the RBC at 90th mins in group I,II,III and IV were determined to be 4.97, 5.63, 4.35 and 4. 15x106/mm3, respectively. Before the experiment, while the haemarocrit values of group I,II,III and IV were determined to be 39.2, 47.2, 40. 7 and 43. 7 % respectively. The same va/ues were found to be 35.6, 42.3, 34.1 and 39.0 %, at the e nd of the hypotensive period. The haematocrit values at 90th mins in group /,ll, lll and IV were determined to be 34.4, 41.3, 30.9 and 28.5 %, respectively. Before the experiment, while the plasma sodium leve/ s in group I,II,III and IV were determined to be 134. 9, 137.9, 137.0 and 141.1 mEq/L, respectively. The same values were found to be 133.5, 136.8, 133.6 and 135.7 mEq/L, at the en d of the hypotensive period, respectively. On the other hand, the plasma sodium values, at 90th min s in group I,II,III and IV were determined to be 136. 6, 136.4, 136. B and 144.3 mEq/L, respectively. Before the experiment, the plasma potassium /eve/s in group I,II,III and IV were determined to be 4.98, 5.27, 5.07 and 5.06 mEq/L, respectively. At the end of the hypotensive period, the plasma potassium levels in the all groups increased. At 90th mins these values in the all groups decreased.